2022
DOI: 10.1177/00033197221115562
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Systemic Inflammation Index and No-Reflow Phenomenon in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: This study aimed to evaluate the relationship between no-reflow phenomenon and systemic inflammation index (SII) and to compare the predictive capacity of SII together with the neutrophil–lymphocyte ratio (NLR), and the platelet–lymphocyte ratio (PLR) in patients with ST-elevation myocardial infarction (STEMI). A total of 785 patients were included. The thrombolysis in myocardial infarction (TIMI) flow degree has been used to describe the no-reflow phenomenon. The study population was divided into two groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…However, few studies have investigated the relationship between SII and no-reflow. An article 6 reported that SII may be a promising indicator for the prediction of no-reflow in patients with STEMI; this is consistent with the conclusions made by Çelik et al 1 We have some comments regarding the article by Çelik et al 1 They should provide medication information because drugs (eg, ticagrelor and clopidogrel) can affect the SII. 7 In Çelik's article, although multivariable regression analysis suggested that SII has great statistical significance, the odds ratio (OR) was relatively small (OR = 1.212).…”
Section: Dear Editorsupporting
confidence: 77%
See 4 more Smart Citations
“…However, few studies have investigated the relationship between SII and no-reflow. An article 6 reported that SII may be a promising indicator for the prediction of no-reflow in patients with STEMI; this is consistent with the conclusions made by Çelik et al 1 We have some comments regarding the article by Çelik et al 1 They should provide medication information because drugs (eg, ticagrelor and clopidogrel) can affect the SII. 7 In Çelik's article, although multivariable regression analysis suggested that SII has great statistical significance, the odds ratio (OR) was relatively small (OR = 1.212).…”
Section: Dear Editorsupporting
confidence: 77%
“…7 In Çelik's article, although multivariable regression analysis suggested that SII has great statistical significance, the odds ratio (OR) was relatively small (OR = 1.212). 1 Besides, the predictive ability of SII was not significantly different from that of NLR (.789 vs .766) or PLR (.789 vs .759). 1 The mechanisms by which SII may participate in the noreflow phenomenon remain unclear.…”
Section: Dear Editormentioning
confidence: 77%
See 3 more Smart Citations